Analysis of Grade Ten English Textbook from Cultural Perspective - Subedi, Lok Nath (Kalika Journal of Multidisciplinary Studies, 2024)
The main aim of the study on “An Analysis of Grade ten English Textbook from Cultural Perspective” is to explore the cultural aspects that includes in newly revised Compulsory English textbook. This study mainly focuses on cultural aspects that includes on this book such as religions, celebrations, customs, rituals, genders, castes, clothes, food items, arts and literary genres. The primary source of this study was the newly revised textbook of class ten. The collected data were observed, analyzed and interpreted qualitatively. The study found that the textbook writers have included various contents concerning to the cultures from the world. The study found that the textbook includes the new technologies as well as religions, customs, rituals etc. However, the textbook is not seem completely justifiable regarding the inclusion of female writers, representation of minority and marginalized group of people and their languages and other activities concerning to their cultures.